Energy flow in men`s javelin throw and its relationship to joint load and performance - Köhler, H.-P.; Witt, M. (PeerJ, 2023)
Background Performance in javelin throwing is dependent on the release speed and therefore the energy transferred to the javelin. Little is known about the flow of mechanical energy in javelin throwing and whether there is a connection to joint loading and throwing performance. The purpose of the study was therefore to investigate (1) the energy flow within the kinetic chain of the throwing arm, (2) how it is related to performance and joint loads and (3) how joint forces and torques are used to transfer, generate and absorb mechanical energy.